1,25(OH)2D3 Strengthens the Vasculogenesis of Multipotent Mesenchymal Stromal Cells from Rat Bone Marrow by Regulating the PI3K/AKT Pathway - Ye B; Weng Y; Lin S; Lin J; Huang Z; Huang W; Cai X (Dove Medical Press, 2020)
Bozhi Ye, 1,* Yawen Weng, 2,* Shuang Lin, 1 Jiahui Lin, 3 Zhouqing Huang, 1 Weijian Huang, 1 Xueli Cai 1 1Department of Cardiology, The Key Lab of Cardiovascular Disease of Wenzhou, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 2Department of Pediatrics, The Second School of Medicine, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China; 3The First School of Medicine, Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xueli CaiDepartment of Cardiology, The Key Lab of Cardiovascular Disease of Wenzhou, The First Affiliated Hospital of Wenzhou Medical University, 2 Fuxue Road, ZheJiang 325000, People’s Republic of ChinaEmail cardiosherry@126.comWeijian HuangDepartment of Cardiology, The Key Lab of Cardiovascular Disease of Wenzhou, The First Affiliated Hospital of Wenzhou Medical University, 2 Fuxue Road, ZheJiang 325000, People’s Republic of ChinaEmail weijianhuang69@126.comBackground: Multipotent mesenchymal stromal cells (MSCs) have recently been reported to promote vasculogenesis by differentiating into endothelial cells and releasing numerous cytokines and paracrine factors. However, due to low cell activity, their potential for clinical application is not very satisfactory. This study aimed to explore the effects and mechanisms of 1,25-dihydroxyvitamin D (1,25(OH) 2D 3) on the vasculogenesis of MSCs.Methods: MSCs were isolated from the femurs and tibias of rats and characterized by flow cytometry. After treatment with different concentrations of 1,25(OH) 2D 3 (0 μM, 0.1 μM and 1 μM), the proliferation of MSCs was analyzed by Cell Counting Kit-8 (CCK-8), and the migratory capability was measured by Transwell assays and cell scratch tests. Capillary-like structure formation was observed by using Matrigel. Western blotting was used to detect the expression of FLK-1 and vWF to investigate the differentiation of MSCs into endothelial cells. Western blotting and gelatin zymography were used to detect the expression and activities of VEGF, MMP-2 and MMP-9 secreted by MSCs under the influence of 1,25(OH) 2D 3. Finally, the VDR antagonist pyridoxal-5-phosphate (P5P) and the PI3K/AKT pathway inhibitor LY294002 were utilized to test the phosphorylation levels of key kinases in the PI3K/AKT pathway by Western blotting and the formation of capillary-like structures in Matrigel.Results: The proliferation and migratory capability of MSCs and the ability of MSCs to form a tube-like structure in Matrigel were enhanced after treatment with 1,25(OH) 2D 3. Moreover, MSCs treated with 1,25(OH) 2D 3 showed high expression of vWF and Flk-1. There was a significant increase in the expression of VEGF, MMP-2 and MMP-9 secreted by MSCs treated with 1,25(OH) 2D 3, as well as in the activity of MMP-2 and MMP-9. The phosphorylation level of AKT increased with time after 1,25(OH) 2D 3 treatment, while LY294002 weakened AKT phosphorylation. In addition, the ability to form capillary-like structures was reduced when the VDR and PI3K/AKT pathways were blocked.Conclusion: This study confirmed that 1,25(OH) 2D 3 treatment can strengthen the ability of MSCs to promote vasculogenesis in vitro, and the mechanism may be related to the activation of the PI3K/AKT pathway.Keywords: multipotent mesenchymal stromal cells, 1,25-(OH) 2D 3, vasculogenesis, vitamin D receptor, PI3K/AKT pathway